Means-Tested Transfers in the US: Facts and Parametric Estimates - Nezih Guner; Christopher Rauh; Gustavo Ventura (Institute of Labor Economics (IZA), 2024)
How substantial are means-tested transfers in the United States? How have these transfers evolved over time, and what is their impact on the income distribution? We use microdata from the Survey of Income and Program Participation to document the scope of the main means-tested programs for households headed by working-age adults. We report key features of these programs, their generosity, and coverage by household income, marital status, and the number and age of children in the household. We also assess the role of the transfer system in reducing income inequality and document its changing magnitude and effects in recent years. Finally, we provide parametric estimates of transfers as a function of income and household characteristics for use in applied work in macroeconomics and public finance.
Keywords: E62; H24; H31; 330; means-tested transfers; households; income inequality; parametric estimates